Structural, Electrical, and Optical Effects of Metal Doping on ZnO Thin Films. Issue 12 (2nd May 2019) - Huber, Silvia; Mardare, Cezarina Cela; Kleber, Christoph; Hassel, Achim Walter
Abstract : Doped ZnO thin films are prepared by reactive co‐sputtering of ZnO and a metal (Mn, Ti, W, and Zr). Structural and morphological analysis is done by means of SEM/EDX, XRD, and AFM. Electrical properties in terms of Volta potential are determined via Scanning Kelvin Probe (SKP), UV–VIS spectroscopy is employed to investigate optical properties. Band gaps Eg are obtained using Tauc plots. Doping of ZnO led to significant differences regarding structural, electrical, and optical properties. Morphology of doped ZnO tends to be smoother and more compact, as compared to the pristine ZnO. XRD measurements proved that W doped ZnO films exhibit an amorphous structure, whereas a secondary phase present in the Mn doped ZnO is strongly suggested. W and Mn as dopants lead also to special band gap positions in UV spectroscopy. W:ZnO exhibits a higher value for Eg whereas band gaps of Ti:ZnO and Zr:ZnO are similar to pristine ZnO. For Mn:ZnO two band gaps can be obtained. One is slightly higher and the other one is significantly lower than the one of pristine ZnO. Volta potential doubled when ZnO is doped with W, Zr, or Ti as compared to the pristine ZnO. Mn doped ZnO resulted in a lower Volta potential than pristine ZnO. Abstract : Doped ZnO thin films are prepared by reactive co‐sputtering of ZnO and a metal: Mn, Ti, W, and Zr. Doping leads to significantly different structural, electrical, and optical properties. Doped ZnO films exhibit lower surface roughness. The W:ZnO thin film is amorphous, whereas a second phase is supposed to be present in Mn:ZnO.